The role of acoustic radiation force impulse imaging in the diagnosis of cervical carcinoma (Annals of Medical Research, 2021)
Aim: To investigate the diagnostic value of acoustic radiation force impulse imaging in the detection of cervical cancer, and to assess the contribution of this imaging method in distinguishing histological subtypes of cervical carcinoma.Materials and Methods: Twenty four patients with malignant cervical mass and 25 healthy volunteers were included in this prospective study. Ultrasonographic evaluation were performed using a 3.5–6-MHz convex abdominal transducer and adequate software for performing elastographic examinations in quantitative acoustic radiation force impulse mode (Virtual Touch Quantification®). Every examination consisted of at least three independent shear wave velocity measurements. The mean shear wave velocity values were calculated, and used for statistical analysis. Postoperative pathology results of the lesions were used as the reference standard.Results: The mean shear wave velocity values were calculated as 2.79±1.03 m/s in cervical carcinomas, and as 1.86±0.62 m/s in control group. The mean shear wave velocity value of cervical carcinomas was significantly higher than the control group (p=0.003). The mean shear wave velocity values in squamous carcinoma, adenocarcinoma, and adenosquamous carcinoma subtypes were calculated as 2.78±0.93 m/s, 3.16±1.46 m/s, and 1.90±0.21 m/s, respectively. There were no significant differences between cervical carcinoma subtypes in terms of their shear wave velocity values (p=0.247).Conclusion: Acoustic radiation force impulse imaging is a non-invasive and cost-effective, promising adjunct modality that enables objective quantitative measurement, which may contribute to the diagnosis of malignant cervical masses.
Keywords: Acoustic radiation force impulse; ARFI; cervical carcinoma; ultrasonography